(untitled) (Archive of Conferences, 2021)
In world practice, it is considered as the only integrated component of the international supply chain system for trucks. Their effectiveness is considered to be the achievement of the synergistic effect of their interrelated components. It is well known that synergy is a science and technology aimed at increasing the efficiency of distribution, production and sales in the field of logistics in the face of other methods of management. Their structurally mutually beneficial coordination in the delivery of goods and information flows and provides an icon to reduce stagnation due to the appropriate increase in the competitiveness of the enterprise, which is also very important in times of crisis